2011
DOI: 10.3340/jkns.2011.50.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Halo-Vest Immobilization and Surgical Fusion of Odontoid Fractures

Abstract: or HVI may provide adequate support in type II fracture or type III stable fractures. Posterior fixation of C1-2 achieves higher fusion rates compared to conservative treatment, but is a challenging surgical technique and results in limitations in the cervical range of motion after surgery 5,17,18,22) . Anterior fixation techniques such as direct anterior odontoid screw fixation preserve rotatory motion of the cervical spine, with immediate stabilization of the spine 8,12,24,25) . In this study, we retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…However, CTJ treatment is a safe and cheap technique in the management of type II odontoid fractures without any complications. Kim et al reported 20 weeks for time to fusion in surgically treated patients and 17.6 weeks in patients treated with the CH; that is, they concluded that surgical patients had a shorter bone-healing time than patients who received a CH (16). The mean bone-healing time was 7.2 weeks in the present study (a range of 4-16 weeks).…”
Section: Discussionsupporting
confidence: 56%
“…However, CTJ treatment is a safe and cheap technique in the management of type II odontoid fractures without any complications. Kim et al reported 20 weeks for time to fusion in surgically treated patients and 17.6 weeks in patients treated with the CH; that is, they concluded that surgical patients had a shorter bone-healing time than patients who received a CH (16). The mean bone-healing time was 7.2 weeks in the present study (a range of 4-16 weeks).…”
Section: Discussionsupporting
confidence: 56%
“…Type II fractures involve the base of the odontoid and do not extend into the C2 body and unstable associated with a nonunion rate of at least 32% with nonoperative treatment. [11][12][13] Odontoid fractures can causes the atlantoaxial instability, which may cause neck pain and stiffness, activity limitation, and progressive compression of the spinal cord. [14,4,15] As another special fractures of axis, Hangman's fractures was the pedicles fractures of C2 which may led to traumatic spondylolisthesis of the axis.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative management, a regular practice in earlier days, was later followed by prolonged application of halo vest. These techniques invariably lead to non union of the fracture and furthermore caused major discomfort to the patients 1, 2 . It was Nakanishi and Bohler who initially described odontoid screw placement for type II odontoid fractures 3 .…”
Section: Introductionmentioning
confidence: 99%